Quebrada de la Sal magnetoestratigraphic section, Los Colorados Formación, Upper Triassic Ischigualasto-Villa Unión basin, Argentina - Santi Malnis, Paula (2011)
Ischigualasto-Villa Union basin is a continental rift developed in southwestern quarter of Pangea throughout the Triassic. Los Colorados Formation, its youngest stratigraphic unit, is formed by a continuously succession of red beds that host a paleovertebrate assemblage of biostratigraphic importance. In this work are presented the results of the first magnetostratigraphic study applied on Los Colorados Formation with the aim of global correlations. For this, a full section of 600 meters were sampled. The paleomagnetic results show two components, recognized as “A” and “C”. Component C has unblocking temperature from 650°C, presents inter-site consistency and was identify as the carrier of the primary remanent magnetization with an SSW-down (reverse polarity) or NNE-up (normal polarity) orientation in different sites. The main magnetic mineral carrier is hematite and only approaches reaches saturation from 2.0 T. The magnetostratigraphic column of Los Colorados presents 16 magnetozones of normal and reverse polarity. In conjunction with published volcanic ash dates, the preferred polarity correlation for Los Colorados Formation magnetostratigraphy is between magnetochrons E7r (227 Ma) and E14n (216215 Ma) from Newark Basin GPTS, or early to middle Norian. This result is the first step to tune the position of Los Colorados Fm. in Late Triassic Pangea.